Measurements of the mechanical response of unidirectional 3D-printed PLA - Tagarielli,V; song,Y; li,Y; song,W; yee,K; lee,KY (Materials & Design, 2017)
Fully dense PLA blocks were manufactured by 3D-printing, depositing a polymer filament in a single direction via the fusion deposition method (FDM). Specimens were cut from printed blocks using conventional machining and were used to perform tension, compression and fracture experiments along different material directions. The elasto-plastic material response was found to be orthotropic and characterised by a strong tension-compression asymmetry; the material was tougher when loaded in the extrusion direction than in the transverse direction. The response of the unidirectional, 3D-printed material was compared to that of homogeneous injection-moulded PLA, showing that manufacturing by 3D-printing improves toughness; the effects of an annealing thermal cycle on the molecular structure and the mechanical response of the material were assessed.